Recycling method of composite material containing polyurethane foam - WANG GUOSHU; ZHU WEIZHEN; GUO HUANXIANG; LI GUOWEI (2017)
The invention provides a recycling method of a composite material containing polyurethane foam. The polyurethane foam, glass fibers, fabrics and other materials in the composite material are separated through alcoholysis reaction, a liquid recovered material obtained by utilizing alcoholysis and isocyanate are prepared into a polyurethane adhesive, and a solid recovered material is bonded to prepare a novel composite polyurethane material, so that the composite polyurethane material complicated in composition is recycled, and the recycling problem of the composite material containing the polyurethane foam is solved. 本发明提供种含有卷帙泡沫的复合材料的回收利用方法，通过醇解反应分离聚氨酯复合材料中的聚氨酯泡沫和玻纤、面料等材料，并利用醇解得到的液体回收物与异氰酸酯制成聚氨酯胶，粘接固体回收物，制成新的聚氨酯复合材料，使成分复杂的聚氨酯复合材料得到回收利用，解决了含有聚氨酯泡沫的复合材料的回收利用难题。